Looking into the labyrinth of gender inequality: women physicians in academic medicine. Issue 10 (25th September 2018) - Han, Heeyoung; Kim, Yujin; Kim, Sehoon; Cho, Yonjoo; Chae, Chungil
Abstract : Context: Gender inequality remains prevalent worldwide in academic medicine. A closer look into women physicians' gendered experiences through the lens of culture is necessary to advance understanding of gender inequality in this context. Relatively few studies, however, have investigated how social and cultural practices implicitly yet significantly affect gender inequality throughout women physicians' careers. Objectives: This study aimed to investigate the lived experiences of South Korean women physicians working in academic medicine and to focus on social and cultural influences on the gendered process of their career journeys. The study will extend our understanding of gender inequality in academic medicine through an in‐depth analysis of social and cultural practices that affect the phenomenon. Methods: We conducted a qualitative study utilising a grounded theory approach. Twenty‐one women physicians participated in semi‐structured interviews. Data were recorded, transcribed and analysed through a process of constant comparison using grounded theory to extract themes. Results: Junior women physicians were more vulnerable to gender discrimination and channelled to 'ghettos' through the seniority‐based, patriarchal, collectivist and business hospital culture in South Korea. Under pressure to excel at work, they had no work–family balance and experienced identity crises as competent doctors and mothers. They felt themselves to be 'othered' in multiple cultural contexts, including school ties, rankism and a culture of after‐work gatherings. Minimal levels of leadership aspiration created a vicious cycle of a lack of social networking and mentoring. Pursuing individual excellence, they attributed their struggles to personal choices and rarely sought organisational support. Conclusions: The dynamics of cultural and social practices constantly and implicitly recreate mechanisms to maintain gender inequality in academic medicine in South Korea. Planned culture changes at individual, organisational and national levels are imperative to discontinue the vicious cycle that exists in the labyrinth of women physicians' career development in academic medicine. Abstract : The authors report that cultural and social practices, such as seniority and hospital business culture, constantly and implicitly recreate mechanisms to maintain gender inequality in Korean academic medicine.